THE LEXICAL PROCESS OF ACEHNESE BORROWING - Rizka, Budi (Getsempena English Education Journal, 2017)
The aims of this study were to analyze the process of lexical borrowing in Acehnese. The subjects of the study were 30 textbooks in Acehnese language of Language Centre of Aceh. Qualitative method is the way to find the data with useful the interactive model as its analyzing done. The finding of lexical process of borrowing in Acehnese was found three types, they are loan-words which adopt 57 lexicons, loan-blend adopts 101 lexicons, and loan-translation adopts the 19 lexicons.Â  The adoption of Acehnese lexical has 177 lexicons where percentage of lexical borrowing of noun (78.53%), adjective (15.25%), verb (5.09%), and adverb (1.13%) similarly that the noun is the largest count in borrowing process of any aspect such politic, industry, or religion.Keywords: lexical process, borrowing, Acehnese.